잣버섯(Neolentinus lepideus) 에탄올 추출물의 혈당상승 억제 효과 - 신자원; Jawon Shin; 배상민; Sangmin Bae; 한상민; Sangmin Han; 이윤혜; Yunhae Lee; 김정한; Jeonghan Kim; 지정현; Jeonghyun Ji; et al. (Hangug gynnhaghoi ji, 2015)
버섯을 이용하여 새로운 혈당상승 억제 물질을 개발하여 건강 기능성 식품 소재 산업에 응용하고자 느타리버섯, 노랑느타리버섯, 분홍느타리버섯, 새송이버섯과 잣버섯들의 α-glucosidase 저해활성을 측정한 결과 잣버섯 자실체의 에탄올 추출물이 가장 높은 α-glucosidase 저해활성을 보였다. 잣버섯 자실체 분말을 95% 에탄올로 30oC에서48시간 추출하였을 때 α-glucosidase 저해물질이 가장 많이 추출되었고이 α-glucosidase 저해물질을 함유한 잣버섯 에탄올 추출물은 일반 쥐와 streptozotocin으로 당뇨를 유발시킨 당뇨 쥐에서 모두 농도 의존적으로 식후 혈당상승 억제 효과를 보였다. For development a new anti-diabetic compound from edible mushroom, antihyperglycemic α-glucosidase inhibitory activities of Pleurotus ostreatus, Pleurotus cornucopiae, Pleurotus salmoneostramineus, Pleurotus eryngii and Neolentinus lepideus were investigated on its water and ethanol extracts. α-Glucosidase inhibitory activity of Neolentinus lepideus fruiting body showed the highest at 86.3% in the 95% ethanol extracts and water extract from Pleurotus cornucopiae was also higher at 48.5% among water extracts. Therefore, Neolentinus lepideus which showed very high α-glucosidase inhibitory activity was selected as a new anti-diabetic agent-containing mushroom and the α-glucosidase inhibitor was maximally extracted when treated with 95% ethanol at 30oC for 48 hr. The ethanol extracts from Neolentinus lepideus fruiting body showed dosage-dependent hypoglycemic action after administration to 120 min in the SD-rat and streptozotocin-induced diabetic SD-rat.